Implications of The Increase In The Government's Project Budget Ceiling For Construction Managerial In Small Qualified Contractors - Elsanema, Oktri; Ophiyandri, Taufika; Hidayat, Benny (Universitas Negeri Padang, 2024)
The government has issued LKPP regulation No. 11 of 2021 which states that small qualification contractors may handle projects up to 15 billion, which before this regulation came out small contractors could only handle projects with a maximum value of 2,5 billion. The government hopes positively for this restriction, because the gap between large and small construction companies is quite high. In order to compete for large project values, small contractors must be able to reorganize the four managerial stages of construction project implementation, namely Planning, Organizing, Actuating, and Controlling (POAC). For this reason, a study was conducted that aims to analyze the implications of increasing the budget ceiling of government projects on the construction managerial of small qualification contractors. This research uses a descriptive qualitative method by analyzing changes in construction project managerial at each stage of construction project managerial through an in-depth interview process directly with small contractors who handle construction projects worth 5 to 15 billion in fiscal years 2022 and 2023 in the Padang City government. The result of this research is that there are changes in the managerial constructors at the planning stage. At the planning stage the contractor organizes the implementation of the project so that the project can be completed within the agreed time, through the use of Man, Money, Material, Market, Machine, and Method (6M) resources. The resources that change during project implementation at the planning stage are human resources (man). With an increase in the project budget ceiling, small qualification contractors increase the number of team personnel, labor, and team competence in mastering certain competencies to support the implementation of construction projects. While the management of 5M (man, money, material, machine, and method) at the organizing, actuating, and controlling stages, small qualification contractors are able to adjust their construction managerial implementation when the project is still worth under 2,5 billion with a project whose value increases to 15 billion.